Biological characterization of chemically diverse compounds targeting the Plasmodium falciparum coenzyme A synthesis pathway - Fletcher, Sabine (Parasit Vectors, 2016)
BACKGROUND: In the fight against malaria, the discovery of chemical compounds with a novel mode of action and/or chemistry distinct from currently used drugs is vital to counteract the parasite’s known ability to develop drug resistance. Another desirable aspect is efficacy against gametocytes, the sexual developmental stage of the parasite which enables the transmission through Anopheles vectors. Using a chemical rescue approach, we previously identified compounds targeting Plasmodium falciparum coenzyme A (CoA) synthesis or utilization, a promising target that has not yet been exploited in anti-malarial drug development. RESULTS: We report on the outcomes of a series of biological tests that help to define the species- and stage-specificity, as well as the potential targets of these chemically diverse compounds. Compound activity against P. falciparum gametocytes was determined to assess stage-specificity and transmission-reducing potential. Against early stage gametocytes IC(50) values ranging between 60 nM and 7.5 μM were obtained. With the exception of two compounds with sub-micromolar potencies across all intra-erythrocytic stages, activity against late stage gametocytes was lower. None of the compounds were specific pantothenate kinase inhibitors. Chemical rescue profiling with CoA pathway intermediates demonstrated that most compounds acted on either of the two final P. falciparum CoA synthesis enzymes, phosphopantetheine adenylyltransferase (PPAT) or dephospho CoA kinase (DPCK). The most active compound targeted either phosphopantothenoylcysteine synthetase (PPCS) or phosphopantothenoylcysteine decarboxylase (PPCDC). Species-specificity was evaluated against Trypanosoma cruzi and Trypanosoma brucei brucei. No specific activity against T. cruzi amastigotes was observed; however three compounds inhibited the viability of trypomastigotes with sub-micromolar potencies and were confirmed to act on T. b. brucei CoA synthesis. CONCLUSIONS: Utilizing the compounds we previously identified as effective against asexual P. falciparum, we demonstrate for the first time that gametocytes, like the asexual stages, depend on CoA, with two compounds exhibiting sub-micromolar potencies across asexual forms and all gametocytes stages tested. Furthermore, three compounds inhibited the viability of T. cruzi and T. b. brucei trypomastigotes with sub-micromolar potencies and were confirmed to act on T. b. brucei CoA synthesis, indicating that the CoA synthesis pathway might represent a valuable new drug target in these parasite species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-016-1860-3) contains supplementary material, which is available to authorized users.